Soils and Cultural Layer of Voznesenskoye I Settlement - Aleksandr L. Aleksandrovsky (Археология евразийских степей)
The article examines the processes of cultural layer formation and their relationship with lithological, soil-forming, and other exogenous phenomena, which together constitute a unified natural-anthropogenic complex of processes. The soil profile at the Voznesenskoye I settlement consists of a series of genetically interconnected horizons: sod (AO), humus (AY, gray-humus), eluvial (EL, podzolic), and textural (BT, illuvial). These horizons formed during the Holocene within a lithologically heterogeneous stratum that accumulated in the Late Pleistocene. Despite the relatively shallow thickness of the cultural layer at Voznesenskoye I settlement, two chronological horizons have been identified at the site: the Late Bronze Age and the transition from the Final Bronze Age to the Early Iron Age. The artifacts are associated with different soil and lithological horizons and have some stratigraphic isolation. In the lower layer, dating to the Late Bronze Age, net-impressed pottery is present, often featuring pits and comb-stamp impressions. Higher up, in the layer marking the transition from the Final Bronze Age to the Early Iron Age, net-impressed pottery is found, primarily decorated with pits and dots, and only rarely with comb-stamp impressions. A more detailed description of the site's archaeological material is provided in the article by A.V. Novikov. In a redeposited state, within the cultural deposits of the Late Bronze Age–Early Iron Age, Mesolithic stone artifacts are occasionally found. Of particular note is the Object No. 1—a pit fill from the initial stage of the Early Iron Age, which cuts through the Bronze Age horizon and lies at the base of the cultural layer. The fill exhibits elevated levels of phosphorus and calcium, associated with the presence of bone remains. The same sample also shows increased concentrations of copper and zinc.